Outside directors and board advising and monitoring performance - Kim, Kyonghee; Mauldin, Elaine; Patro, Sukesh (Journal of Accounting and Economics, 2014)
Divergent views exist about whether boards must tradeoff advising for monitoring performance when utilizing outside versus inside directors. We suggest a dichotomous tradeoff focus underestimates outside directors׳ impact on board performance. We find outside director tenure positively associated with firm acquisition/investment policy advising performance and CEO compensation monitoring performance, suggesting that advising and monitoring do not always compete for directors׳ time. However, tenure is not a panacea – it marginally weakens financial reporting monitoring performance which is instead enhanced by outside directors׳ financial expertise. Overall, the results suggest outside director tenure and diverse expertise support both advising and monitoring performance.